Prevalence Of Rifampicin Resistance in New Cases Of Pulmonary Tuberculosis In Children - Sonia Saleem; Aneela Shaheen; Muhammad Naeem; Shahid Mehmood Sahi; Sara Rubab; Bint-Ul- Huda (Journal of Rawalpindi Medical College)
Objective: The research aims to determine the prevalence of rifampicin resistance in newly diagnosed pediatric pulmonary tuberculosis cases, investigating the frequency of resistance to this first-line antibiotic. By doing so, it seeks to provide insights into rifampicin's effectiveness as a treatment and contribute to understanding drug-resistant tuberculosis in children.